Spectral Identification Characteristics of Typical Rocks and Minerals in Alkali Feldspar Granite Type Nb-Ta Deposits in Central Inner Mongolia - Feicui WANG; Daming WANG; Xusheng LI; Bo ZHANG; Jialin WEI; Siqi CAO; Yunxiao TONG (Yankuang ceshi)
Located in the central region of Inner Mongolia, within the southern segment of the Daxing’anling-North China Craton metallogenic belt, the area is notable for its widespread distribution of alkaline granite-type niobium-tantalum (Nb-Ta) deposits. Despite the region’s rich Nb-Ta resources, a comprehensive understanding of its spectroscopic characteristics remains inadequate, hindering precise and efficient mineral exploration. This study focuses on the Zhaojinggou large Nb-Ta deposit, employing portable short-wave infrared and thermal infrared spectrometers to analyze typical rock and mineral samples. The research reveals distinctive spectroscopic features of Nb-Ta enriched albite granite, amazonitization albite granite, amazonite pegmatite, biotite monzogranite, and wolframite-quartz vein. Comparative analysis, particularly against the standard sodium granite spectrum from the USGS spectral library, identifies a specific weak absorption feature at 2360nm, crucial for distinguishing amazonitization albite granite from other rocks and minerals, likely attributed to rock alteration and mineralization processes. In thermal infrared spectroscopy, quartz veins containing wolframite are distinguished by their high reflectance and “three-peak” features. Despite their similar spectral shapes, Nb-Ta enriched albite granite, amazonite pegmatite, and biotite monzogranite can be distinguished by the absorption depth and the ratio of absorption peak intensity around 2200nm. These findings provide a foundational dataset for future remote sensing surveys and evaluations of Nb-Ta mineral resources. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202401090001.